Pengaruh Asam Askorbat Pada Laju Korosi Baja St 37 - I Gusti Made Sanjaya, (Matematika dan Sains, 2009)
The aim of research was to study the role of ascorbic acid as inhibitor to corrosion rate of steel of St 37, a steel with low carbon that has strong and tough properties. That organic compound was adsorb on surface and form thin layer that able to protect metal from oxidation. Inhibitor activity of ascorbic acid showed the optimum value at concentration of 60 ppm and maceration time of 10 days with the decreasing of corrosion rate of 47,58 %. Thus ascorbic acid showed the significant effect as inhibitor the corrosion rate of the St 37 steel.